QRIS Socialization as an Effort to Strengthen the Digital Economy And Entrepreneurship - Rahmah Yulisa Kalbarini,M.SEI; Verdianti, M.Sc,Ak; Ema Elisa, M.E.I; Reni Helvira, ME; Hani Meilita Purnama Subardi,M.Ak; Syamratun Nurjannah,M.S.I; Wulan Wahyu Ningrum, M.Ak; Novita, MM; Fitri Jayanti, M.Pd; Anggatia Ariza (Amala Jurnal Pengabdian Kepada Masyarakat, 2025)
In the era of technology 5.0, entrepreneurship needs to be strengthened and QRIS needs to be socialized to support MSMEs and encourage an entrepreneurial spirit. The students and guardians of SMK N Sui Kakap are the intended participants in this program. This activity includes MSME and entrepreneurship seminars, FGDs, and QRIS socialization. This activity shows that entrepreneurship education is essential for accelerating the growth of community knowledge, abilities, and skills as well as for encouraging an inventive and creative attitude. In the era of technology 5.0, entrepreneurship needs to be strengthened and QRIS needs to be socialized to support MSMEs and promote an entrepreneurial spirit. The students and guardians of SMK N Sui Kakap are the intended participants in this program. FGDs, QRIS socialization, and MSME and entrepreneurship workshops make up this activity. This exercise demonstrates how entrepreneurship education is essential for accelerating the growth of community knowledge, abilities, and skills as well as for encouraging an inventive and creative attitude. To achieve good synergy and promote financial inclusion and MSMEs, collaboration is required among academics, the village government, and the business sector.